Bitcoin Security: Evaluating the Efficacy of TLS Protocol in Securing Transactions - Zahraa Yahya Mahdi Al-Mayali (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research study evaluated the efficacy of Transport Layer Security (TLS) protocol in securing Bitcoin transactions against man-in-the-middle attacks. The study used various simulation algorithms to test the effectiveness of TLS in securing Bitcoin transactions. The results of the study showed that the default TLS connection simulation algorithm was highly effective, with a 100% success rate in securing transactions. However, the study also revealed that attackers with fake or valid certificates can still compromise the security of TLS. The study recommends that Bitcoin users take necessary precautions to mitigate the risks associated with man-in-the-middle attacks, such as regularly updating and maintaining SSL/TLS certificates, using strong encryption algorithms, and implementing additional security measures like two-factor authentication. The study concludes that maintaining a strong security posture is crucial for conducting Bitcoin transactions, and stakeholders involved in the Bitcoin ecosystem must remain vigilant and take proactive measures to protect against potential security threats. Future work in this area could focus on exploring alternative encryption algorithms and cryptographic protocols beyond TLS, investigating the use of decentralized security solutions like block chain-based security protocols or distributed trust mechanisms, and examining the use of machine learning and artificial intelligence techniques to improve the detection and prevention of man-in-the-middle attacks in Bitcoin transactions. Overall, the study highlights the importance of continuously exploring new ways to enhance the security and resilience of Bitcoin transactions against potential threats such as man-in-the-middle attacks.